Cambridge practice tests for IELTS - Jakeman, Vanesa. (Tài liệu luyện thi IELTS., 2004)
Introduction; Test 1; Test 2; Test 3; Test 4; General training: reading and writing test A; General training: reading and writing test B; Tapescripts; Answer keys; Model and sample answer sheets.